Orthodontic camouflage: A treatment option - A clinical case report - William Ubilla Mazzini; Fátima Mazzini Torres (Wolters Kluwer Medknow Publications, 2017)
Orthodontic camouflage provides an alternative treatment for angle III malocclusion since patients with limited economic resources cannot opt for orthognathic surgery, it being clear that correction will be achieved at the dental level and not at the bone complex. Objective: To determine an alternative treatment for patients who do not have the possibility of having orthognathic surgery. Clinical case: A 13-year-old female patient, dolico facial biotype with slightly concave profile, with Class III Skeletal by mandibular prognathism, anterior crossbite, anterior diastema, and large mandibular body, molar class, and canine III. Alexander technique brackets were placed; premolar extraction was not planned. Once the case was completed, the correction of the anterior crossbite was achieved, thanks to the use of the spaces that existed at the beginning of the treatment and also that a correct distalization of canines and retraction of the lower anterior segment were performed.